2015
DOI: 10.1097/prs.0000000000000807
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Chemotherapy and Radiation Therapy on the Remodeling of Acellular Dermal Matrices in Staged, Prosthetic Breast Reconstruction

Abstract: Background An acellular dermal matrix (ADM) used in prosthetic breast reconstruction will typically incorporate, in time, with the overlying mastectomy skin flap. This remodeling process may be adversely impacted in patients that require chemotherapy and radiation therapies that influence neovascularization and cellular proliferation. Methods Multiple biopsies of the submuscular capsule and ADM were procured from 86 women (N=94 breasts) undergoing exchange of a tissue expander for a breast implant. These wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 117 publications
0
13
0
Order By: Relevance
“…Furthermore, it has already been shown that radio- or chemotherapy had an influence on implanted ADMs (Alloderm), resulting in a limited ADM modeling [20]. …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has already been shown that radio- or chemotherapy had an influence on implanted ADMs (Alloderm), resulting in a limited ADM modeling [20]. …”
Section: Discussionmentioning
confidence: 99%
“…After AMD implantation, neovascularization occurs between 1 and 6 months postoperatively [7]. During this period, most patients undergo chemo-and/ or RT, which has already been shown to limit ADM remodeling [19]. In our study, 45.8% of all complications occurred between 2 weeks and 6 months.…”
Section: Discussionmentioning
confidence: 51%
“…However, the severity of capsular contracture rate is reportedly less with acellular dermal matrix (ADM) [5] reflecting some animal studies [6,7]. Chemotherapy independently can adversely affect the type 1 collagen thereby affecting the remodelling and integration of ADM [8].…”
Section: Literature Review and Proposed Chart Component Discussionmentioning
confidence: 99%